Hubungan Disiplin Belajar dengan Prestasi Belajar Siswa Kelas V SD Negeri 25 Mattirowalie Kecamatan Tanete Riattang Barat Kabupaten Bone - Makmur Nurdin; Sri Rahayu Ningsih; Adnan K Adnan K (Universtas Negeri Makassar, 2021)
: This study is a correlational study that aims to determine whether or not there is a relationship between learning discipline and learning achievement of fifth grade students at SD Negeri 25 Mattirowalie, Tanete Riattang Barat District, Bone Regency. The population in this study were all fifth grade students of SD Negeri 25 Mattirowalie, Tanete Riattang Barat District, Bone Regency. while the number of samples in this study were 47 students. Data collection is done by providing questionnaires and documentation. The data analysis technique used in this research is descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive analysis obtained 102 learning disciplines and a percentage of 84.62% in the very good category and student achievement with an average of 84.40 and a percentage of 84.80% in the very good category. The results of inferential statistical analysis obtained tcount (7.9180) ttable (1.67943) at a significant level of 5%. Thus H0 is rejected and H1 is accepted. It can be concluded that there is a significant relationship between learning discipline and learning achievement of fifth grade students at SD Negeri 25 Mattirowalie, Tanete Riattang Barat sub-district, Bone Regency.